Bibliometric Analysis of UAV/Drone Maintenance Publications - Prasidananto Nur Santoso; Eko Poerwanto; Lazuardy Rahendra Pinandhita; Yasrin Zabidi; Uyuunul Mauidzoh; Fajar Khanif Rahmawati (Institut Teknologi Dirgantara Adisutjipto, 2026)
This study highlights the lack of comprehensive studies on UAV (Unmanned Aerial Vehicle) and drone maintenance, despite numerous bibliometric studies conducted in other fields. This knowledge gap on this crucial aspect of UAV technology necessitates an in-depth analysis of the existing literature. The primary objective of this study is to conduct a bibliometric analysis of publications related to UAV/drone maintenance to map the literature, identify trends, and highlight contributions from different countries, universities, and authors. The analysis was conducted by collecting metadata from 30 years of academic publications (1994–2024) indexed in databases such as Scopus, and using VOSViewer to visualize the bibliometric network. Expected outcomes include identification of the most influential publications, authors, and journals, mapping research trends, and insights into collaboration opportunities between researchers and institutions. These findings are expected to guide future research by providing research topic recommendations to address existing literature gaps. Overall, this study offers a comprehensive overview that enriches the literature and encourages significant innovation in UAV/drone maintenance.